O dilema biopolítico: negacionismo biopolítico e reapropriação biopolítica - Ádamo Bouças da Veiga (O Que Nos Faz Pensar)
This paper compares two different positions regarding contemporary biopolitics, with special focus (but not exclusively) on the management of COVID-19’s pandemic.  We detected two different positions or strategies in this respect that we shall name, respectively, biopolitical reappropriation and biopolitical negationism. The first will be examined through Paul. B. Preciado’s work and the second through Agamben’s pandemics texts. We will proceed by the displaying of the concept of biopolitics in its Foucauldian origin  and in some later developments.  Secondly, we will analyze Preciado’s and Agamben’s resistance strategies. Finally, we conclude that Agamben’s strategy leads to a suicidal necropolitics , as the Brazilian pandemic management testifies, and that Preciado’s position displays a broad horizon of possible and valid resistances to contemporary biopolitics.